Development of Low-Lactose Probiotic Yogurt Drinks with Lactiplanti-bacillus plantarum subsp. plantarum Dad-13: Physicochemical and Sensory Characteristics - Rendra Lebdoyono; Tyas Utami; Endang Sutriswati Rahayu; Dian Anggraini Suroto (Applied Food Biotechnology, 2023)
Background and Objective: Lactose intolerance is a prevalent clinical syndrome due to consumption dairy products. Development of low-lactose products may help consumers to receive nutrition of dairy products without negative health effects. The aim of this study was to investigate survival, physicochemical and sensory characteristics of low-lactose yogurt drinks produced with probiotic Lactiplantibacillus plantarum subsp. plantarum Dad-13 during cold storage.